FAKTOR-FAKTOR PENYEBAB RENDAHNYA AKTIVITAS REMAJA MASJID DI KELURAHAN AIR DINGIN, KOTA PEKANBARU - Yahya, Muhammad; Ayub, Daeng; Jais, Muhammad (Journal of Practice Learning and Educational Development, 2026)
This study aims to identify the factors causing the low level of mosque youth activities in Air Dingin Subdistrict, Bukit Raya District, Pekanbaru City. This research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation involving mosque youth members, mosque administrators, community leaders, and parents. The findings indicate that the low level of mosque youth activities is influenced by internal and external factors, including low motivation and religious awareness, weak organizational management, full-day school activities, lack of parental support, limited funding and facilities, the influence of social media, and weak coordination between mosque youth organizations and mosque management. Therefore, integrated guidance, innovative programs, and strengthened collaboration among mosque youth, mosque administrators, families, and the community are needed to revitalize mosque youth activities